Activin and Nodal Are Not Suitable Alternatives to TGFβ for Chondrogenic Differentiation of Mesenchymal Stem Cells. (October 2017) - Kroon, Laurie M. G. de; Davidson, Esmeralda N. Blaney; Narcisi, Roberto; Farrell, Eric; Kraan, Peter M. van der; van Osch, Gerjo J. V. M.
Objective: Previously, we demonstrated the importance of transforming growth factor-β (TGFβ)-activated SMAD2/3 signaling in chondrogenesis of bone marrow–derived mesenchymal stem cells (BMSCs). However, TGFβ also signals via the SMAD1/5/9 pathway, which is known to induce terminal differentiation of BMSCs. In this study, we investigated whether other SMAD2/3-activating ligands, Activin and Nodal, can induce chondrogenic differentiation of BMSCs without inducing terminal differentiation. Design: Activation of SMAD2/3 signaling and chondrogenesis were evaluated in human BMSCs ( N = 3 donors) stimulated with TGFβ, Activin, or Nodal. SMAD2/3 activation was assessed by determining phosphorylated-SMAD2 (pSMAD2) protein levels and SMAD2/3-target gene expression of SERPINE1 . Chondrogenesis was determined by ACAN and COL2A1 transcript analysis and histological examination of proteoglycans and collagen type II. Results: Both Activin and TGFβ enhanced pSMAD2 and SERPINE1 expression compared to the control condition without growth factors, demonstrating activated SMAD2/3 signaling. pSMAD2 and SERPINE1 had a higher level of expression following stimulation with TGFβ than with Activin, while Nodal did not activate SMAD2/3 signaling. Of the 3 ligands tested, only TGFβ induced chondrogenic differentiation as shown by strongly increased transcript levels of ACAN and COL2A1 and positive histological staining of proteoglycans and collagen type II. Conclusions: Even with concentrations up to 25 times higher than that of TGFβ, Activin and Nodal do not induce chondrogenic differentiation of BMSCs; thus, neither of the 2 ligands is an interesting alternative candidate for TGFβ to induce chondrogenesis without terminal differentiation. To obtain stable cartilage formation by BMSCs, future studies should decipher how TGFβ-induced terminal differentiation can be prevented.